1976
DOI: 10.1177/107769907605300201
|View full text |Cite
|
Sign up to set email alerts
|

Agreement with Opinionated TV Characters across Cultures

Abstract: Canadian adults see less humor and realism in Bunker show than does U.S. sample. Dogmatism is related to agreement with Archie.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Both studies found that, compared to U.S. viewers, individuals from other countries were less likely to watch the program. Both Tate and Surlin (1976) and Vidmar and Rokeach (1974) reported that foreign audiences found the show to be lacking in humor and realism.…”
Section: Selective Exposurementioning
confidence: 95%
“…Both studies found that, compared to U.S. viewers, individuals from other countries were less likely to watch the program. Both Tate and Surlin (1976) and Vidmar and Rokeach (1974) reported that foreign audiences found the show to be lacking in humor and realism.…”
Section: Selective Exposurementioning
confidence: 95%
“…A cross-cultural analysis by Tate and Surlin did reveal a greater appreciation of the humor in All in the Family by Americans than by Canadians (18). However, Vidmar and Rokeach did not find a significant difference between the American and Canadian subgroups concerning the perceived degree of humor in All in the Family (20).…”
mentioning
confidence: 86%
“…Meyer found that the physical aspects of the characters, role stereotypes, and comedy behavior, a n d not the "views of life" espoused by the characters, are the aspects of the show which dominate the perceptions of six-to-ten year old children (10). A cross-cultural analysis by Tate and Surlin did reveal a greater appreciation of the humor in All in the Family by Americans than by Canadians (18). However, Vidmar and Rokeach did not find a significant difference between the American and Canadian subgroups concerning the perceived degree of humor in All in the Family (20).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Such research has, however, shown that viewers frequently prefer media characters and programs which support their beliefs or behaviors (e.g., Vidmar and Rokeach, 1974;Tate and Surlin, 1976;Surlin and Tate, 1976;Brigham and Giesbrecht, 1976;Wilhoit and deBock, 1976;Atkin et al, 1979). Selective exposure is more readily 1 The present research emerges out of another study concerning a specially created TV program ("The Great American Values Test") that we designed to bring about increases in egalitarian and proenvironmental beliefs and behavior.…”
mentioning
confidence: 90%